Strategi Manajemen Humas Dalam Membangun Citra Di Sekolah Dasar NU Hasyim Asy’ari Kotalama Malang - Annur, Irkham Rois (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
The school's relationship with the community is essentially a means that plays a role in fostering and developing the personal growth of students in school. Schools and communities have a very close relationship in achieving school or educational goals effectively and efficiently. Educational institutions, especially schools, cannot be separated from management, because management is an intergal component that cannot be separated from the overall educational process. This study aims to determine: (1) How to plan public relations management strategy in building image in NU Hasyim Asy'ari Elementary School Kotalama Malang. (2) How to implement supporting and inhibiting factors as well as public relations management strategy solutions in building image in Elementary School NU Hasyim Asy'ari Kotalama Malang. (3) What are the results of the public relations management strategy in building an image at the NU Hasyim Asy'ari Elementary School Kotalama Malang. The results showed that (1) The development of public relations management strategies in building the image at the NU Hasyim Asy'ari Elementary School Kotalama Malang was carried out and carried out by the deputy public relations officer and public relations staff in the formulation of the plan. (2) The implementation of supporting and inhibiting factors as well as public relations management strategy solutions in building an image at the NU Hasyim Asy'ari Elementary School in Kotalama Malangh carried out several programs, namely understanding the internal and external conditions of the school, improving physical and non-physical conditions, introducing school to the community. (3) Constraints and solutions to the development of public relations at the Mohammad Hatta Islamic Elementary School, there is no special staff who handles the media, lack of coaches in the academic field, disapproval of some of the community towards the program held by the school, the solution is to recruit special staff who handle this.